Estudio comparativo del modelo educativo japonés como base para el desarrollo económico y social de Colombia (2021)
According to the US News and World Report, Colombia is classified like one of the worst Latin American countries in education, ranking 56 in the PISA 2018 report, in comparison to Japan which is among the best in the position 13th. Based on the data presented and the others topics that will be addressed inside the study, it will look for to answer the question: ¿Why should a country like Colombia with an infinity of advantages compared to Japan stay in the lowest position of education, being one of the factors that influence the level of underdevelopment on the country.